Penyusunan Aplikasi Penilaian Proses Pembelajaran Sederhana - Hendra Lesmana; Mewa Zabeta; E.I Pusta Siligar; Lilik Masamah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
This Community Service aims to provide knowledge to teachers and prospective teachers about preparing simple applications for assessing the learning process; provide guidance to teachers and prospective teachers regarding the preparation of simple applications in assessing the learning process; create a temporary special forum or forum for preparing simple applications for assessing the learning process; and provide motivation to teachers and prospective teachers regarding the preparation of simple applications in assessing the learning process. Participants in Community Service are teachers from partner schools or schools assisted by the East OKU Muhammadiyah Association, prospective teachers, and other participants from outside partner schools with a total of 115 participants. Activities were carried out using a workshop format via the zoom meeting application. The activity ran smoothly and the participants seemed enthusiastic about taking part in the workshop activities.